The Genesis of East Asia, 221 B.C.-A.D. 907 - Holcombe, Charles, 1956- (Association for Asian Studies and University of Hawai'i Press, 2001)
The Genesis of East Asia examines in a comprehensive and novel way the critically formative period when a culturally coherent geopolitical region identifiable as East Asia first took shape.
Keywords: East Asia -- History.; Extrême-Orient -- Histoire.; 15.75 history of Asia.; HISTORY -- General.; HISTORY -- Asia -- General.; East Asia; Ostasien; China; Natievorming.; Geschichte 221 v. Chr.-907.; History